(untitled) (Psychology Travelogs, 2023)
The article substantiates the importance of the formation of soft skills and emotional intelligence in the context of studying at a higher education institution. The struggle to get a job and keep it is getting harder because of shifting educational patterns, the flexibility of educational programs, and the abundance of highly skilled workers. Students are forced to supplement their hard talents with soft skills to show their actual potential to get an advantage over rivals. When compared to soft skills, which are self-developed, interactive, communicative, human, and transferrable capabilities, it has been proved that hard skills are academic abilities, experience, and degree of competence. This is very important nowadays to know the answer to the question of what is meant by the term soft skills and emotional intelligence. The article draws on various sources in literature to define the concept and it has been explored how soft skills and EI are important to everyone in every context. It entails the involvement of personal aspects within any relationship. Soft skills are important to students, as they are linked to job performances and career development; they are crucial for employees who need to manage their interactions and emotions to interact effectively with customers and get engaged with the workplace missions; for management and leadership skills, as they help lead teams towards common and shared goals, accomplish organizational missions and support organizations in their future directions and visions.